2022
DOI: 10.1002/adhm.202200782
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable and Antioxidant DNA Hydrogel as a Cytokine Delivery System for Diabetic Wound Healing

Abstract: Impaired diabetic wound healing is associated with the persistence of chronic inflammation and excessive oxidative stress, which has become one of the most serious clinical challenges. Wound dressings with anti-inflammatory and reactive oxygen species (ROS)-scavenging properties are desirable for diabetic wound treatment. In this study, a shape-adaptable, biodegradable, biocompatible, antioxidant, and immunomodulatory interleukin-33 (IL-33)-cytogel is developed by encapsulating IL-33 into physically cross-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Under diabetic conditions, immune cells can generate excessive ROS, which impedes wound healing. It has been reported that scavenging excess ROS promotes the regeneration of DWs. , DNA molecules are sensitive to a variety of ROS radicals and possess scavenging capabilities. , To verify this, we used methylene blue (MB) as a hydroxyl radical (•OH) indicator to test the ROS-scavenging activity of DNA. Hydroxyl radicals were generated by the Fenton reaction and then incubated with the Y monomer, AgNCs-Y, and the L monomer for 30 min each.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Under diabetic conditions, immune cells can generate excessive ROS, which impedes wound healing. It has been reported that scavenging excess ROS promotes the regeneration of DWs. , DNA molecules are sensitive to a variety of ROS radicals and possess scavenging capabilities. , To verify this, we used methylene blue (MB) as a hydroxyl radical (•OH) indicator to test the ROS-scavenging activity of DNA. Hydroxyl radicals were generated by the Fenton reaction and then incubated with the Y monomer, AgNCs-Y, and the L monomer for 30 min each.…”
Section: Resultsmentioning
confidence: 99%
“…(2) IL-10, one of the most potent immune modulators, activates the transition of macrophages from pro-inflammatory M1 to anti-inflammatory M2 phenotype, which is encapsulated in Agilegel’s pores and plays an anti-inflammatory role. (3) VEGF- α is covalently conjugated to the L DNA monomer through the strong interaction of biotin–streptavidin (SA), which is used to improve vascular development and promote angiogenesis. , In addition, DNA structures themselves are sensitive to various ROS and serve as effective ROS scavengers …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations